2019
DOI: 10.3390/jcm8111957
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Liquid Biopsy Based on Circulating Tumor DNA

Abstract: Many types of cells secrete DNA, RNA, and proteins through microvesicles, such as exosomes and apoptotic bodies, for the purpose of extracellular communication [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…LSLC-specific mutation signatures that are carried by LSLC-EXO may serve as clinical liquid biopsy biomarkers for cancer diagnostics and prognostics 35 . Although numerous studies showed that cancer specific mutations could be detected in circulating tumor DNA 36 38 , few studies have explored the signatures of exosomal genetic variants in cancer. To examine whether genetic variants in cancer cells at RNA level were also present in their derived exosomes, we performed variant calling analysis by Genome Analysis Tool Kit (GATK) using our Ribo-zero RNA-seq data.…”
Section: Resultsmentioning
confidence: 99%
“…LSLC-specific mutation signatures that are carried by LSLC-EXO may serve as clinical liquid biopsy biomarkers for cancer diagnostics and prognostics 35 . Although numerous studies showed that cancer specific mutations could be detected in circulating tumor DNA 36 38 , few studies have explored the signatures of exosomal genetic variants in cancer. To examine whether genetic variants in cancer cells at RNA level were also present in their derived exosomes, we performed variant calling analysis by Genome Analysis Tool Kit (GATK) using our Ribo-zero RNA-seq data.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, liquid biopsy concerning breast ductal fluid, breast milk, seminal fluid, cervical and vaginal secretions, and uterine/utero-tubular lavage can improve the management of various genital cancers of men as well as women [ 31 , 32 , 33 , 34 , 35 , 36 ]. Several other liquid biopsy samples including tear fluid, sweat, wound efflux, amniotic fluid or bronchoalveolar and peritoneal lavage can also provide benefits for the patient and healthcare at large [ 7 , 9 , 37 , 38 ]. Therefore, an increasing evidence shows that various types of liquid biopsy, illustrated in Figure 1 , have the potential in cancer diagnostics, disease stratification, and monitoring of response to therapeutic interventions and could replace invasive tissue biopsy.…”
Section: Liquid Biopsy Classificationmentioning
confidence: 99%
“…Traditionally strong is an application of biomarkers related to the blood-based biopsy. However, increasing evidence demonstrates that the application of complementary types of liquid biopsy is crucial for the overall quality of diagnostics [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The current article highlights very recent progress made in the area and provides prominent examples of a spectrum of liquid biopsy approaches with great potential to benefit several patient cohorts and to improve overall healthcare quality.…”
Section: Introductionmentioning
confidence: 99%